2015
DOI: 10.1080/21663831.2015.1121165
|View full text |Cite
|
Sign up to set email alerts
|

Cavity Evolution at Grain Boundaries as a Function of Radiation Damage and Thermal Conditions in Nanocrystalline Nickel

Abstract: Enhanced radiation tolerance of nanostructured metals is attributed to the high density of interfaces that can absorb radiationinduced defects. Here, cavity evolution mechanisms during cascade damage, helium implantation, and annealing of nanocrystalline nickel are characterized via in situ transmission electron microscopy (TEM). Films subjected to self-ion irradiation followed by helium implantation developed evenly distributed cavity structures, whereas films exposed in the reversed order developed cavities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Cavity formation can lead to volumetric swelling. Recent work by Muntifering et al [43] suggested only a limited reduction of swelling in pulsed laser deposited nanocrystalline Nickel.…”
Section: Comparison Of Nanocrystalline Grains With Fine Grains and Implications For Swellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Cavity formation can lead to volumetric swelling. Recent work by Muntifering et al [43] suggested only a limited reduction of swelling in pulsed laser deposited nanocrystalline Nickel.…”
Section: Comparison Of Nanocrystalline Grains With Fine Grains and Implications For Swellingmentioning
confidence: 99%
“…Bai et al [25] demonstrated an enhanced defect annihilation process through rapid interstitial defect absorption and reemission (and subsequent combination) with vacancies approaching grain boundaries. A large scatter of defect densities as a function of grain size has been observed, however, which has been attributed to the dependence of boundary sink efficiency on grain boundary character [27] and other interfacial deviations [43].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, concurrent irradiations of materials with both a range of ion species and energies are needed to simulate these complex environments. Studies have examined the mobility of dislocations in Fe in the presence of He, 60 bubble growth and linkage behavior in SiC, 61 void formation in Ni, 62 and the dependence of single, dual, and triple ion beam (helium/deuterium/gold) irradiation on cavity formation and evolution. 63 Overall, in situ TEM irradiation has proven one of the most consistent and reliable tools for the investigation of the transient, ion-induced effects on materials at the nanoscale.…”
Section: Electron and Positron Beam Characterization Techniquesmentioning
confidence: 99%
“…30 In situ TEM He implantation has previously been performed on several pure metals. [31][32][33][34][35][36][37][38][39][40][41] In situ TEM annealing has been employed to determine cavity growth mechanisms in He-implanted metals. 40,[42][43][44] We present new experimental results of in situ TEM He implantation and subsequent in situ TEM annealing in Pd, a face-centered cubic metal.…”
Section: Introductionmentioning
confidence: 99%